PENGARUH EMOTIONAL QUOTIENT DAN IKLIM ORGANISASI TERHADAP MOTIVASI KERJA DI PT SATNUSA PERSADA TBK - Calvin, Calvin; Suhardi, Suhardi (LPPM Universitas Putera Batam, 2021)
This study aims to determine the effect of organizational climate on work motivation, emotional quetient on work motivation. This research was conducted at PT Satnusa Persada TBK in the Batam area with as many as 110 workers as respondents. Based on the results of data processing and sample testing, it was found that: (1)There is an influence of organizational climate on work motivation, (2)there is an effect of emotional quetient on work motivation, (3)emotional quetient and organizational climate together affect work motivation. Companies with a good organizational climate and emotional quetient will have a positive and significant effect in increasing employee motivation.